Optimization and standardization of the work of a health care facility during a chemical accident - O.V. Hudoshyna; N.V. Kurdil (Medičnì Perspektivi)
During the years of war, as a result of aviation and missile attacks, a significant number of health care facilities in various regions of Ukraine were destroyed, and the complexity and intensity of their work increased significantly. If the readiness of hospitals and their employees to treat gunshot and explosive injuries is established, in the case of mass destruction of chemically hazardous enterprises and the threat of the enemy using weapons of mass destruction, including chemical weapons, there is a need for special training of health care facilities to work in the in conditions of chemical threats. The aim of the work was justification of the development and set of measures for the implementation of standard operating procedures in the event of a chemical incident. The legal documents and recommendations of the Ministry of Health of Ukraine, management of the World Health Organization and the Red Cross on the topic of the study were used. The research methods: bibliosemantic, analytical, modeling were applied. It is established that the special management group, which includes representatives of various services, is of decisive importance in the effective management of a health care facility during a chemical incident: administration; communication department; security department; management of nurses and the department of infection control; human resources department; pharmacy; intensive care unit; department of engineering maintenance and repair; laboratory; kitchen; laundry; cleaning service and waste management. The most important measures of response to a chemical incident that ensure the safety of medical personnel and patients are the organization of a triage zone and a decontamination area for chemically affected persons. Based on the above, to prepare a health care facility for work during a chemical incident, it is necessary to develop a response plan, which consists of special administrative and management decisions and provides for regular staff training.